2020
DOI: 10.1007/s11356-020-10040-7
|View full text |Cite
|
Sign up to set email alerts
|

Do males and females respond differently to ocean acidification? An experimental study with the sea urchin Paracentrotus lividus

Abstract: Seawater pH lowering, known as ocean acidification, is considered among the major threats to marine environment. In this study, post-spawning adults of the sea urchin Paracentrotus lividus were maintained at three pH values (8.0, 7.7, 7.4) for 60 days. Physiological, biochemical, cellular, behavioural and reproductive responses were evaluated in males and females. Significant differences between sexes were observed, with higher ammonia excretion and lower catalase activity in males. Respiration rate (after 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 112 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…OA had negative effects on gonad growth, maturation, egg size, and gamete development in some echinoderm species (Siikavuopio et al, 2007;Kurihara, 2008;Stumpp et al, 2012;Kurihara et al, 2013;Suckling et al, 2014;Suckling et al, 2015;Verkaik et al, 2016;Dworjanyn and Byrne, 2018;Hu et al, 2018;Hue et al, 2020;Marcěta et al, 2020;Anand et al, 2021), while other studies reported no change in gamete development and quality (Wood et al, 2008;Uthicke et al, 2013;Hazan et al 2014; Uthicke et al, 2014;Dell'Acqua et al, 2019;Karelitz et al, 2019;Wong et al, 2019;Hue et al, 2020;Uthicke et al, 2020).…”
Section: Gametogenesis and Gamete Qualitymentioning
confidence: 91%
“…OA had negative effects on gonad growth, maturation, egg size, and gamete development in some echinoderm species (Siikavuopio et al, 2007;Kurihara, 2008;Stumpp et al, 2012;Kurihara et al, 2013;Suckling et al, 2014;Suckling et al, 2015;Verkaik et al, 2016;Dworjanyn and Byrne, 2018;Hu et al, 2018;Hue et al, 2020;Marcěta et al, 2020;Anand et al, 2021), while other studies reported no change in gamete development and quality (Wood et al, 2008;Uthicke et al, 2013;Hazan et al 2014; Uthicke et al, 2014;Dell'Acqua et al, 2019;Karelitz et al, 2019;Wong et al, 2019;Hue et al, 2020;Uthicke et al, 2020).…”
Section: Gametogenesis and Gamete Qualitymentioning
confidence: 91%
“…For other habitats this relationship ranged between weak positive to moderate negative possibly for the reason that high pH driven waterbodies acidification differentially affect physiology, reproduction, biochemistry, and survival of organisms (McClellan-Green et al, 2007;Ellis et al, 2014;Lane et al, 2015) of those habitats. Especially the female T. ilisha possibly becomes vulnerable to stress from alteration of their resource energy location and high production cost of eggs compared to sperm like of other fish (Marčeta et al, 2020). Moderate positive relationships between GSI and salinity of two saline habitats (Tetulia River and Bay of Bengal) of this study suggest that gonadal development of T. ilisha was promoted by salinity.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, in terms of energy budget, it can be infered that increased respiration and NH 4 + excretion rates with no significant change in feeding rate at high p CO 2 could decrease the amount of energy available for growth and reproduction of the sea urchin. Indeed some previous studies have indicated that exposure of sea urchin to high p CO 2 resulted in a decrease of feeding rate and delay in gonad development 21 , or increased respiration and reduced gonadosomatic index particularly in female sea urchins 35 , 36 . Furthermore, a decrease in the available energy for T. gratilla could be particularly significant under the combination of ocean warming and acidification, considering the significant decrease in feeding rate with the synergistic increase in respiration rate under high temperature and p CO 2 environment, especially when T. gratilla was fed with experimental seagrass.…”
Section: Discussionmentioning
confidence: 97%